Evaluasi Aplikasi Inarisk Menggunakan Indeks Kepuasan Pengguna Berdasarkan Peraturan Menteri Pendayagunaan Aparatur Negara Dan Reformasi Birokrasi Nomor 14 Tahun 2017 - Findi Ayu Sariasih; Edhi Prayitno; Chaerul Bahri; Dhefine Armelsa; Fara Mutia (LPPM STIKOM Tunas Bangsa, 2023)
This study examines the satisfaction of the public towards the inaRISK application, based on the calculation of the Public Satisfaction Index using the guidelines outlined in the Minister of Administrative and Bureaucratic Reform Regulation No. 14 of 2017 regarding the public satisfaction survey on public service delivery. The findings reveal that the calculated index score is 83.46, falling within the range of 76.61 - 88.30, indicating a